The Effectiveness of Mindfulness Based Intervention: Prayer Open Hearts Against Depression in HIV/ AIDS Patients - Siti Latipah; Dewi Prabawati; Wilhelmus Hary Susilo (Jurnal Ilmiah Keperawatan Indonesia [JIKI], 2020)
Acquired Immune Deficiency Syndrome (AIDS) is a group of symptoms that arise due to damage to the human immune system due to infection with the Human Immunodeficiency Virus (HIV). People with HIV will cause stigma in society so that psychosocial problems will arise, one of which is depression. Treatment of depressed patients can be done by non-pharmacological therapy, one of which is Mindfulness-Based Intervention. This study aims to determine the effectiveness of Mindfulness Based Intervention: Open Heart Prayer Against Changes in Depression Levels in HIV / AIDS Patients at RSUD X Tangerang Regency. The research method was a quasy experiment with non-equivalent control group pre- posttest design on 117 samples divided by the control group with 29 samples and the intervention group for 88 samples. Open Heart Prayer Therapy is given 2 times a day for 6 weeks. The independent variables were age, gender, education level, length of diagnosis, stigma and family support. Statistical tests used Wilcoxon, Mann Whitney, and Ordinal Logistic Regression. The results showed that there was a difference in the mean level of depression after being given Mindfulness Based Intervention: Prayer to Open Heart in the intervention and control groups with a significance level of 0.000 <0.05. And there are differences in the level of depression before and after being given Mindfulness Based Intervention: Open Heart Prayer in the intervention group with a significance level of 0.000 <0.05. There is an effect of Mindfulness Based Intervention: Open Heart Prayer on the level of depression with a P Value of 0.040 <0.05. However, there was no significant effect on the level of depression partially with gender p. Value 0.926, education level p value 0.696, long time diagnosed with HIV / AIDS p value 0.076, stigma p value 0.057 and significant effect on family support with p value 0.039. Mindfulness Based Intervention Therapy: Open Heart Prayer is influential and useful in reducing depression levels in HIV / AIDS patients. Keywords: HIV / AIDS; MBI (Prayer of Open Heart); Depression